Evaluation of gonadal macroscopic and microscopic morphometry reveals precocious puberty in Bísaro pig. Issue 12 (14th October 2020) - Paixão, Gustavo; Esteves, Alexandra; Carolino, Nuno; dos Anjos Pires, Maria; Payan‐Carreira, Rita
Abstract: Bísaro pig (BP), like many other local breeds reared in extensive non‐industrial systems, faces many constraints to comply with the EU welfare regulation, particularly regarding the restrictions to surgical castration. In order to adapt an immunocastration protocol to overtake this issue, a puberty timeline is needed. Using gonadal morphometry data from 91 young male BP, this study intended to characterize testicular development, describing the prominent cell types and structures, to ultimately assess the age at puberty in male BP through a mixed prediction model. As expected, the relations between several macro and microscopic parameters and their relation with age were as described within the literature. Post‐pubertal animals have larger and heavier gonads, lower Sertoli cell density/tubule, higher Leydig cell density and larger seminiferous tubules. Meiosis was firstly seen in 44‐day‐old animals, elongated spermatids in 70‐day‐old animals. Complete spermatogenesis was firstly identified in a 90‐day‐old animal. Spermatozoa were present in the epididymis of 23 animals, aged from 70 to 240 days old, and in the vas deferens of 14 animals (105 to 240 days old). The prediction model inferred that male Bísaro pigs reach puberty between 14 and 17 weeks (3 and 4 months old) and become sexually capable from 15 to 19 weeks (3.5 and 4.4 months old). These parameters confirm the sexual precocity of this breed.